Do IFRS Reconciliations Convey Information? The Effect of Debt Contracting - CHRISTENSEN, HANS B.; LEE, EDWARD; WALKER, MARTIN (Journal of Accounting Research, 2009)
ABSTRACT We examine whether earnings reconciliation from U.K. generally accepted accounting principles (GAAP) to International Financial Reporting Standards (IFRS) convey information. As a result of debt contracting, mandatory accounting changes are expected to affect the likelihood of violating existing covenants based on rolling GAAP, leading to a redistribution of wealth between shareholders and lenders. Consistent with this prediction, we find significant market reactions to IFRS reconciliation announcements. These market reactions are more pronounced among firms that face a greater likelihood and costs of covenant violation and early announcements. While the association between later announcements and weaker market reactions is consistent with contractual implications of technical changes to earnings, which investors quickly learn to predict, it is inconsistent with IFRS forcing all firms in the sample to reveal firm‐specific information through accruals. Thus, by showing that mandatory IFRS also affects debt contracting, we expand on existing IFRS research that focuses on how accounting quality and cost of capital are impacted.